Zavajajoči podatki na seznamih ladijskih potnikov kot posledica restriktivne ameriške migracijske zakonodaje - Kulihova, Lucia (Dve domovini, 2019)
The article focuses on American travel and migration legislation in the years 1893, 1903 and 1907, which were intended to manage immigration to the USA. Efforts to limit immigration were based on the criteria of the usefulness of or the potential threat posed by immigrants. The article shows that the data provided in the passen-ger lists were not credible in all cases, since the desire of both immigrants and steamship companies to enter the USA was much stronger than the fear of being refused.
Keywords: 1901-1910; data frauds; emigration; goljufije; izseljevanje; ladijske družbe; legislation; migracijska politika; migracijski zakoni; migration legislation; migration policy; passenger lists; seznami potnikov; steamship companies; USA; zakonodaja; Združene države Amerike